Long-loop reflexes in patients with well-localized cerebrovascular diseases - Takegami, Toru; Takanashi, Yoshiaki; Harashima, Yutaka; Inoue, Yasunori; Motonaga, Takao (Japanese Journal of Stroke, 1988)
Electrical stimulation of the median nerve during voluntary contraction of abductor brevis (APB) muscle produces the direct muscular response (M wave) and a few late responses such as V1 and V2 responses. V2 response (C-response) is considered to be a transcortical long-loop reflex, although the origin and the pathway of this wave are still obscure. We recorded surface EMG of APB muscle and somatosensory evoked potentials (SEPs) simulatneuously in normal subjects and patients with well-localized cerebrovascular diseases to study the supraspinal pathways of V2 response. Surface EMG and SEPs recorded from Erb's point (Erb), the seventh cervical spine (CV7) and the contralateral postrolandic portion (C3 or C4) were averaged when 100-256 electrical stimulation (pulse width : 1 ms, stimulus strength : just above the threshold for M wave) were applied to the median nerve at the wrist. Subjects were asked to contract the APB muscle with constant force (about 1 kg) during recording. In normal subjects, onset and peak latencies of V2 response were 47.2 ± 5.2 ms and 53.1 ± 5.4 ms respectively. N9, P/N13 and N19 components of SEPs appeared with normal latencies. In patients with thalamic lesions, V2 responses and N19 components of SEPs were absent when stimulations were given to the affected side. SEPs obtained from a patient with a lacunar infarction in the posterior limb of the internal capsule appeared normal, while V2 response was not observed by paretic side stimulation. In a patient with a small pontine hemorrhage involving the medial lemniscus at the lower pons, SEP recorded from C3 showed no significant peaks and V2 response was not evoked by affected side stimulation. These results suggest that dorsal column-lemniscal pathway and pyramidal tract might be involved in the pathway of V2 response.